TRENDS IN THE DEVELOPMENT OF ARTIFICIAL INTELLIGENCE IN UKRAINE (Information systems and technologies security, 2020)
In recent years, artificial intelligence technologies have begun to be used in many types of human life: education, medicine, business, finance, management, marketing, industry, etc., and have become a key trend of the time. The article provides information and analyzes the current state and trends in the development of artificial intelligence in Ukraine. An analysis of the strategy for the development of artificial intelligence, which is proposed by a number of ministries, considered the concept of development of artificial intelligence, which is proposed by the State Agency for eGovernment. Data on companies working in the field of artificial intelligence are analyzed and provided. The main activities of Ukrainian companies in the field of artificial intelligence, including a number of Ukrainian startups, have been identified. Provides information on scientific schools and research conducted in the field of artificial intelligence in Ukraine. It is established that the main research focuses on the following areas: neural networks, pattern recognition, mathematical informatics, creation of intelligent information systems and knowledge bases, development of intelligent robotic systems, knowledge-oriented technologies, intelligent search, development of intelligent learning systems, big data analysis, fuzzy systems decision support, multi-agent systems and much more. In general, scientific research conducted in Ukraine in the field of artificial intelligence covers the basis of areas of work that correspond to research in the world. Also in the article the directions of dissertation researches for the last years on intellectual systems and systems of artificial intelligence are analyzed. The main areas in which the dissertation research was performed: intellectual analysis and data processing, knowledge processing and multi-agent technologies, intelligent technologies, including intelligent technologies to support acceptance, image recognition and a number of others.
Keywords: artificial intelligence; development strategy; scientific research; scientific schools; perspectives